Transformational Moments in Social Welfare : What Role for Voluntary Action?. - Brewis, Georgina (Policy Press, 2021)
ePDF and ePUB available Open Access under CC-BY-NC licence. During the consolidation of the welfare state in the 1940s, and its reshaping in the 2010s, the boundaries between the state, voluntary action, the family and the market were called into question. This interdisciplinary book explores the impact of these ‘transformational moments’ on the role, position and contribution of voluntary action to social welfare. It considers how different narratives have been constructed, articulated and contested by public, political and voluntary sector actors, making comparisons within and across the 1940s and 2010s. With a unique analysis of recent and historical material, this important book illuminates contemporary debates about voluntary action and welfare.